From DNA to proteins: the multiple levels of regulation - Tsonis, Panagiotis (Henry Stewart Talks, 2007)
General ideas behind DNA association with: histones, replication, transcription, splicing, RNA modifications, protein synthesis and death and global gene expression analysis